Establishing a Vision, Fostering Prosperity: Transformational Leadership and Psychological Well-Being of Small and Medium Industry Employees - Wijaya, Theo Kusuma Wahyu Adi; Wijono, Sutarto (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Global competition due to the development of information technology is a challenge for Small and Medium Industries (SMIs) to remain competitive. This study aims to determine the correlation between transformational leadership and psychological well-being among SME employees in Tingkir Subdistrict, Salatiga City. The research method used was quantitative with a correlational approach. Participants consisted of 95 employees selected through quota sampling technique. Data were collected using the Multifactor Leadership Questionnaire (MLQ) scale and the Ryff Psychological Well-being scale, then analysed using the Spearman Rho correlation technique. The results showed a positive and significant relationship between transformational leadership and psychological well-being, with a correlation value (r) of 0.858 and a significance of 0.000 (p < 0.05). The higher the application of transformational leadership, the higher the psychological well-being of employees. The implications of this study suggest that transformational leadership can improve employees' psychological well-being, which contributes to increased productivity and company performance. Persaingan global akibat perkembangan teknologi informasi menjadi tantangan bagi Industri Kecil Menengah (IKM) untuk tetap kompetitif. Penelitian ini bertujuan untuk mengetahui korelasi antara kepemimpinan transformasional dengan psychological well-being pada karyawan IKM di Kecamatan Tingkir, Kota Salatiga. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan korelasional. Partisipan terdiri dari 95 karyawan yang dipilih melalui teknik quota sampling. Data dikumpulkan menggunakan skala Multifactor Leadership Questionnaire (MLQ) dan skala Ryff Psychological Well-being, kemudian dianalisis dengan teknik korelasi Spearman Rho. Hasil penelitian menunjukkan adanya hubungan positif dan signifikan antara kepemimpinan transformasional dan psychological well-being, dengan nilai korelasi (r) sebesar 0,858 dan signifikansi 0,000 (p < 0,05). Semakin tinggi penerapan kepemimpinan transformasional, semakin tinggi kesejahteraan psikologis karyawan. Implikasi penelitian ini menunjukkan bahwa kepemimpinan transformasional dapat meningkatkan kesejahteraan psikologis karyawan, yang berkontribusi pada peningkatan produktivitas dan kinerja perusahaan.